Intestinal perforation due to colorectal cancer during pregnancy: case report and literature review - Yan Gao; Yu Sun (BMC, 2024)
Abstract Colorectal cancer (CRC) in pregnancy is sporadic. We reported a case of a woman at 23 + 4 weeks of gestation who presented with abdominal pain. The patient underwent an ultrasound and MRI, during which a colonic mass was noted. Considering a probable incomplete intestinal obstruction, a colonoscopy, biopsy, and colonic stenting were performed by a multidisciplinary team. However, sudden hyperthermia and CT demonstrated intestinal perforation, and an emergency caesarean section and colostomy were conducted. The histological analysis confirmed moderately high-grade adenocarcinoma.